2021
DOI: 10.1111/codi.15491
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of colectomy rates for ulcerative colitis in pre‐ and postbiological eras in Lothian, Scotland

Abstract: Aim Biological treatment is effective in maintaining remission in ulcerative colitis (UC), although the effect on colectomy rates remains unclear. In the UK the use of antitumour necrosis factor and anti‐α4β7 treatments for maintenance therapy in UC was restricted until 2015. The aim of this study was to describe the impact that this change in the prescribing of biologicals had on colectomy rates for UC. Method All patients (adult and paediatric) with a diagnosis of UC who received maintenance biological treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Age-standardised admission rates for IBD have fallen significantly over a period during which there have been substantial increases in biologic use. 6,7 Reassuringly, we have not observed an increase in the risk of severe infection (ITU admission or death) in IBD patients between 2010 and 2020.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Age-standardised admission rates for IBD have fallen significantly over a period during which there have been substantial increases in biologic use. 6,7 Reassuringly, we have not observed an increase in the risk of severe infection (ITU admission or death) in IBD patients between 2010 and 2020.…”
Section: Discussionmentioning
confidence: 59%
“…6,7 We have shown the impact of this in a prevalent IBD population with increased biologic prescribing and reduced surgery rates over time. 2,[6][7][8] However, IBD patients are getting older with increased multimorbidity. It is unknown how these changes in treatment practice impact IBD hospital admission in number, rate and cause.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence regarding UC colectomy rates in recent years is conflicting. Some studies suggest that colectomy rate is decreasing in the era of access to biologic medications 19,20 . However, HES analysis of emergency admissions for UC before the pandemic has demonstrated a decrease in short‐term colectomy rate in recent years that does not persist long‐term 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that colectomy rate is decreasing in the era of access to biologic medications. 19 , 20 However, HES analysis of emergency admissions for UC before the pandemic has demonstrated a decrease in short‐term colectomy rate in recent years that does not persist long‐term. 20 The PROTECT‐ASUC found that the practice of gastroenterologists and colorectal surgeons had changed, with more patients receiving rescue therapy in the form of biologicals, ciclosporin or tofacitinib.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the 1-year colectomy rate of patients with UC receiving anti-TNFs was quite low (1.0%) and similar among anti-TNF agents available in Korea, 5 in line with previous reports. 6 , 7 The major strength of nationwide claims database is to reflect real-world practice. As reported in 2020 inflammatory bowel disease fact sheet in Korea published by the Korean Association for the Study of Intestinal Diseases using the claims data from the National Health Insurance Service, 8 a proportion of UC patients receiving biologics have been increased up to 8% steadily in recent decade while colectomy rates seemed to be declining from 2018 in Korea.…”
mentioning
confidence: 99%